The Structure of News Texts on the School Zoning System: A Study of Kompas.com - Pramesthi, Naila Abyantika; Wijayawati, Dyah; Krisnawati, Vera (Jurnal Bahasa Indonesia Prima (BIP), 2026)
This study is motivated by a suspicion of an imbalance in reporting a particular event. The purpose is to describe the text structure, based on Van Dijk’s model, as used by Kompas.com in the coverage of its school zoning system. This research uses a qualitative approach. The data consist of news articles from Kompas.com on the school zoning system that meet Van Dijk’s analytical criteria. Data are collected through observation, using non-participant observation (SBLC) and note-taking. The text is divided into microstructure, superstructure, and macrostructure, each with several elements. The results show 23 data points in the text structure: 2 macrostructure, 10 superstructure, and 11 microstructure points. The microstructure is the most dominant element. In the microstructure, coherence is most often observed. Kompas frequently emphasizes coherence to ensure unity of meaning and effective message delivery.